Nação e nacionalização na fronteira: as relações político-culturais de Argentina e Brasil com os teuto-brasileiros de Puerto Rico e Porto Novo (1919 - 1945) - Sausen, João Vitor (2022)
In the two final decades of the 19th century, the West of the state of Santa Catarina, the Southwest of Paraná and the current Argentine province of Misiones, were the scenario of a dispute between the Argentine Republic and Brazil. This process ended with a denial of Argentine territorial claims, after the arbitration by the United States of America. However, during the period of litigation, and in the first decades of the 20th century, the region received an intense flow of migrants from different countries, especially the Brazilian state of Rio Grande do Sul, in which we analyzed the case of German-Brazilians. From this process emerged the colonization’s of Puerto Rico, Misiones, and Porto Novo, Santa Catarina, objects of study of this investigation. Based on the notion that German-Brazilians were subjected to nationalizing pressures from two different Nation-States, the present investigation aims to carry out a Comparative History of the political-cultural relationships of Argentina and Brazil with the German-Brazilian populations established in the localities, between the years 1919 and 1945. In order to do so, various sources were used, which allowed us to perceive aspects related to the construction of a public sphere, based on Alejandro Quiroga's conceptions, as well as the establishment of control over cultural manifestations, as well as public policies aimed to the integration of German-Brazilians. In this way, it was possible to perceive that initially the relationship of the Nation-States of Argentina and Brazil with the localities and populations established there was based on the gradual installation of public institutions, which began to occupy spaces that were previously owned by private organizations, or coexisted with them. On the other hand, the context after 1938 marked a transformation of relations, which began to be observed from the perspective of a “German danger”, both in Argentina and in Brazil, which led to the establishment of close surveillance in Puerto Rico and Porto Novo, especially due to the borderland condition of the localities. In addition to leading to more restrictive policies in the cultural environment. It is still necessary to register that the present investigation is inserted in the Frontier, Politics, Society Research Line, of the Postgraduate Program in History of Universidade Federal de Santa Maria, with the area of concentration of History, Power and Culture. The entire research period was financed with a CAPES/DS grant.